Differences among variety samples of Avena strigosa regarding β-glucan, tocopherols, tocotrienols and avenanthramides - Smitterberg, Maria (SLU/Dept. of Food Science, 2013)
Oats (Avena spp.) is a cereal crop mainly used in food and feed applications. Com-mon oats (Avena sativa) has gained attention because of health supporting proper-ties and potential in reducing the risk of chronic diseases, related to its bioactive compounds β-glucan, tocopherols, tocotrienols and avenanthramides. The interest for other species has increased as they may be valuable in food applications due to their contents. Content variations in common oats is well known, but fairly un-known in other species. Previous research showed interesting properties of one relative, Avena strigosa which was investigated in the present study. Variations in the contents of β-glucan, tocopherols, tocotrienols and avenanthramides as well as the molecular weight distribution of β-glucan were studied among thirteen variety samples. Samples from two varieties were subjected to false malting (i.e. exclusion of sprouting) to evaluate effects. There was a significant difference among the samples regarding all studied bioactive compounds (p=0.000). The β-glucan content ranged between 1.9 and 6.3 % (w/w) and the average molecular weight between 1.59×106 and 2.43×106 g/mol. Among studied E-vitamers α-tocotrienol was the highest and varied between 7.4 and 60.0 µg/g DM. Other E-vitamers (α-tocopherol, β-tocotrienol and β-tocopherol) varied between 5.1 and 15.9, 1.3 and 7.2, 0.8 and 3.6 µg/g DM respectively. The main avenanthramides 2c, 2p, 2f and 2fd ranged between 11 and 352, 19 and 211, 7 and 435, from below detection limits to 112 nmol/g DM respectively. The main hydroxycinnamic acid was caffeic acid which varied between 17 and 134 nmol/g DM. The β-glucan content, the average molecular weights of β-glucan, the contents of avenanthramides and hydroxycinnamic acids were affected by false malting, while the contents of E-vitamers were unchanged. Generally, malting lead to a decrease in the content and in the average molecular weight of β-glucan, but caused a pronounced increase in mainly the lately eluted avenanthramides, 2pd and 2fd, especially in samples from one of the two varieties. Even though this study found similarities when comparing A. strigosa and A. sativa certain features were different. The importance of these differences can only be evaluated in human studies which investigate the differences in bioactivity. Further studies are needed to fully evaluate the variation among varieties of A. strigosa and to get a realistic picture of its true potential as a novel oat food crop. Factors to consider should though be the contents of several bioactive compounds and also the responses after processing like malting since the responses may differ between samples. A. strigosa is well worth to investigate further according to the present results.